THE THEORY AND APPLICATION OF THE INDUCTION MOTOR DIAGNOSTIC METHODS BASED ON ELECTRICAL SIGNAL ANALYSIS - Zagirnyak, Mykhailo; Dmytro Mamchur , Dmytro Mamchur; Kalinov, Andrii (Journal of Energy Technology, 2024)
In this article, the theoretical basis and developed hardware and software for an induction motor diagnostic system based on electrical signals analysis is presented. The theoretical principles underlying these methods are based on a spectral analysis of the stator current and power signals. The hardware allows data measurement for different operating modes with different loading of the motors. The software allows making an analysis of preliminary recorded data using motor current signature analysis (MCSA) and instantaneous power spectra analysis (IPSA) methods. Experimental tests with real data analysis showed the possibility of utilising the developed methods and equipment for induction motor diagnostic systems.